Balloon angioplasty and stent implantation within 30 days postcongenital heart surgery (CHS) in children. Issue 12 (23rd October 2022) - Quandt, Daniel; Callegari, Alessia; Niesse, Oliver; Meinhold, Anke; Dave, Hitendu; Knirsch, Walter; Kretschmar, Oliver
Abstract: Objectives: This study aims to assess balloon angioplasty (BAP) and stent implantation (SI) procedures early after congenital heart surgery (CHS) in children. Background: These interventions are considered potential high‐risk procedures and often avoided or postponed. Methods: This is a retrospective, single centre study of all BAP and SI procedures within 30 days after CHS (01/2001 until 01/2021). Results: A total of 127 (96 SI, 31 BAP) procedures were performed in 104 patients at median 6.5 days (interquartile range: 1–15) after CHS. Balloon‐to‐stenosis ratio and balloon‐to‐reference vessel ratio were significantly smaller compared to stent‐to‐stenosis ratio and stent‐to‐reference vessel ratio ( p  < .001 and p  = .005). There was a greater rise in absolute vessel diameter, greater rise in vessel diameter in relation to the stenosis and vessel diameter in relation to the reference vessel with SI ( p  < .001, p  = .01, and p  < .001). Up to 94% SIs fulfilled both success criteria (increase of vessel diameter ≥50% of minimal vessel diameter or achievement ≥75% of the reference vessel diameter). Major adverse events were more frequent in the BAP group ( p  = .05). Intraprocedural complications were 5/31 (16%) in the BAP group and 13/96 (13%) in the SI group ( p  = .77). Conclusion: BAP and SI procedures within 30 days post‐CHS can be performed safely, with a greater stent‐to‐stenosis ratio and a greater rise in vessel diameter with stent implantation.